2020
DOI: 10.1088/2053-1591/ab6259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sr addition on microstructures and mechanical properties of Mg-1Zn-1Ca-xSr alloys

Abstract: The Sr-containing magnesium alloys have unique characteristics and demonstrate potentials to broaden the application of magnesium alloys. The microstructures and room temperature tensile properties of the as-cast Mg-1Zn-1Ca-xSr (x=0.1, 0.5, 1.5, 2.5 weight%) alloys were investigated in this study. The results indicated that the grains of the Sr-containing alloys were gradually refined and the quantity of second phases was obviously increased with increasing the Sr content. In addition, the phase constituents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Numerous additional investigations employed FTIR analysis as a characterization method to study the crystalline nature of produced BAG powders. 74,72,77,46,72 Thermal investigation of BAG powder using concurrent differential thermal analysis (DTA) and thermogravimetry (TG) revealed that sintering at temperatures over 900 °C is required to generate crystalline BAG. 72 Najafinezhad et al 78 Aside from the capacity of BAG ceramic to generate apatite, SEM and inverted fluorescence microscopy pictures of grown human osteoblast cells (HOB) demonstrated a better cell spread on BAG discs in relation to calcium silicate.…”
Section: Fabrication Methods and Characteristics Of Baghdaditementioning
confidence: 99%
See 2 more Smart Citations
“…Numerous additional investigations employed FTIR analysis as a characterization method to study the crystalline nature of produced BAG powders. 74,72,77,46,72 Thermal investigation of BAG powder using concurrent differential thermal analysis (DTA) and thermogravimetry (TG) revealed that sintering at temperatures over 900 °C is required to generate crystalline BAG. 72 Najafinezhad et al 78 Aside from the capacity of BAG ceramic to generate apatite, SEM and inverted fluorescence microscopy pictures of grown human osteoblast cells (HOB) demonstrated a better cell spread on BAG discs in relation to calcium silicate.…”
Section: Fabrication Methods and Characteristics Of Baghdaditementioning
confidence: 99%
“…The structure of BAG ceramics generated with a density of 3.48 g/cm 3 , was explored with diameters less than 100 nm through electron microscopy images. Spheric structures were also investigated in other studies …”
Section: Fabrication Methods and Characteristics Of Baghdaditementioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31][32] TiN-PVD was also combined with traditional plasma nitriding and chemical vapor deposition techniques. [33][34][35] Moreover, the morphological surface defects were also resolved using a duplex technique, which is a combination of PVD and cathodic cage plasma nitriding (CCPN) as employed by Imran Bashir on Al substrate. [36] Improved hardness and wear resistance by using combined TiN-PVD with CCPN were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy, in the last decades, has shown to be a very useful tool for studying many different types of materials, such as thin films [ 1 ], gels [ 2 ], carbon-based materials [ 3 , 4 ], layered semiconductors [ 5 ], polymers [ 6 ], materials of biological [ 7 ] interest, and also for cultural heritage [ 8 ] issue. Sometimes, when Raman features are very low in intensity or are not detectable at all, it is possible to make the analyte contact a particular surface that is usually made up of a noble metal, which is able to enhance Raman signals by using an effect due to the interaction between the light and the plasmonic surface on the analyte [ 9 ].…”
Section: Introductionmentioning
confidence: 99%